2018
DOI: 10.1186/s12906-018-2377-4
|View full text |Cite
|
Sign up to set email alerts
|

Utilization of Chinese medicine for respiratory discomforts by patients with a medical history of tuberculosis in Taiwan

Abstract: BackgroundTuberculosis (TB) is one of the world’s major communicable infectious diseases, and it still imposes a great health burden in developing countries. The development of drug-resistant TB during the treatment increases the treatment complexity, and the long-term pulmonary complications after completing treatment raise the epidemic health burden. This study intended to investigate the utilization of Chinese medicine (CM) for respiratory symptoms by patients with a medical history of TB in Taiwan.MethodsW… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 76 publications
0
6
0
Order By: Relevance
“…These findings suggest that patients tend to use complementary medicine. Previous research has shown that in general, Asians use complementary medicine in addition to conventional medicine ( 23 ). In addition, community's influence plays a strong role in TB medication in Asia.…”
Section: Discussionmentioning
confidence: 99%
“…These findings suggest that patients tend to use complementary medicine. Previous research has shown that in general, Asians use complementary medicine in addition to conventional medicine ( 23 ). In addition, community's influence plays a strong role in TB medication in Asia.…”
Section: Discussionmentioning
confidence: 99%
“…The Ma-Xing-Shi-Gan-Tang, consisting of Ephedra , semen Pruni armeniacae , licorice and gypsum , is generally used to treat lung heat. Previous studies on Ma-Xing-Shi-Gan-Tang focus on treating chronic obstructive pulmonary disease, allergic rhinitis and tuberculosis [14] , [15] , [16] . Ma-Xing-Shi-Gan-Tang has been reported to have antitussive and antipyretic effects, which may be due to the inhibition of histaminergic and acetylcholinergic receptors that activate both sympathomimetic α- and β-adrenergic receptors [17] .…”
Section: Discussionmentioning
confidence: 99%
“…Although Western medicine is the mainstream in Taiwan, about 30% of patients have used TCM to treat problems and diseases of the major human organ systems recognized by Western medicine 17 . Several studies have reported on TCM uses among patients with different diseases, based on analysis of the NHIRD 18‐21 …”
Section: Discussionmentioning
confidence: 99%